DRY CONSTRUCTION MIXED FOR FOAM CONCRETE (Academicia Globe: Inderscience Research, 2022)
Autoclaved foam concrete is a multifunctional building material.  The production technology is much simpler and the equipment used in production requires less metal and energy consumption.  The properties of foam concrete can be improved and controlled depending on the place of use and climatic conditions of use.  Therefore, its properties are variable over a large range.